On the Concept of Energy: Conservation and Transformation versus Equivalence - RICARDO LOPES COELHO (Metaichmio Publications, 2012)
Many studies have shown that the concept of energy is a problem for teaching. It is in general taught that energy can neither be created nor destroyed but only transformed. Based on the original papers of the discoverers of energy, it will be shown in the present paper that these discoverers did not find anything which is indestructible and transformable. In distinguishing between the treatment of phenomena and the theories carried out by the discoverers of energy, it can be concluded that they established equivalences between different domains, such as motion and heat or position and motion. Taking this idea of equivalence, it will be finally shown that some of the problems pointed out by science teaching experts can be overcome.